A FOXO1-induced oncogenic network defines the AML1-ETO preleukemic program - Lin, Shan (Blood, 2017)
Understanding and blocking the self-renewal pathway of preleukemia stem cells could prevent acute myeloid leukemia (AML) relapse. In this study, we show that increased FOXO1 represents a critical mechanism driving aberrant self-renewal in preleukemic cells expressing the t(8;21)-associated oncogene AML1-ETO (AE). Although generally considered as a tumor suppressor, FOXO1 is consistently upregulated in t(8;21) AML. Expression of FOXO1 in human CD34(+) cells promotes a preleukemic state with enhanced self-renewal and dysregulated differentiation. The DNA binding domain of FOXO1 is essential for these functions. FOXO1 activates a stem cell molecular signature that is also present in AE preleukemia cells and preserved in t(8;21) patient samples. Genome-wide binding studies show that AE and FOXO1 share the majority of their binding sites, whereby FOXO1 binds to multiple crucial self-renewal genes and is required for their activation. In agreement with this observation, genetic and pharmacological ablation of FOXO1 inhibited the long-term proliferation and clonogenicity of AE cells and t(8;21) AML cell lines. Targeting of FOXO1 therefore provides a potential therapeutic strategy for elimination of stem cells at both preleukemic and leukemic stages.